Wola . pismo Międzyzakładowego Komitetu Koordynacyjnego, no. 235, 1986 - John Paul II; Jarosławski, Juliusz; Urbański, Andrzej; Zieliński, Andrzej; Zalewski, Maciej; Stasiński, Piotr (MKK Wola, 1986)
Print run: 2000-12000 copies